2010
DOI: 10.1007/s10452-010-9324-x
|View full text |Cite
|
Sign up to set email alerts
|

A study on the effects of food quantity and quality on glutathione S-transferase (GST) activity and growth rate parameters of Daphnia carinata varying in age

Abstract: The adverse influences of insufficient food and toxins on Daphnia carinata's body growth, reproduction and tolerance were investigated in the laboratory. Different concentrations of Scendesmus obliquus and a mixture of S. obliquus and microcystin (MC)-containing Microcystis aeruginosa PCC7820 were used to feed D. carinata. Glutathione S-transferase (GST) activity towards five chemical compounds (substrates) was measured and used as an indicator of their tolerance. Body growth rate and clutch size of D. carinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…However, the total activity of mGST is lower than that of sGST, as is, presumably, its contribution to the detoxification. Similarly, in Daphnia carinata, decreasing GST (total) with age was associated with higher mortality and reduced tolerance towards toxic cyanobacteria (Guo and Xie, 2011).Even though D. magna is a model organism for freshwater studies, it is important not to generalize into other detoxication pathways or to toxins of different molecular structure, as Kozlowski-Suzuki et al (Kozlowski-Suzuki et al, 2009) did not find a clear relationship between GST and tolerance in copepods towards toxic phytoplankton (the dinoflagellates Alexandrium minutum, A. tamarense and Prorocentrum lima, and the haptophyte Prymnesium parvum). In their study, the phytoplankton contained nodularin, toxins causing paralytic shellfish poisoning and diarrhetic shellfish poisoning, and ichthyotoxins with haemolytic activity instead of MC.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…However, the total activity of mGST is lower than that of sGST, as is, presumably, its contribution to the detoxification. Similarly, in Daphnia carinata, decreasing GST (total) with age was associated with higher mortality and reduced tolerance towards toxic cyanobacteria (Guo and Xie, 2011).Even though D. magna is a model organism for freshwater studies, it is important not to generalize into other detoxication pathways or to toxins of different molecular structure, as Kozlowski-Suzuki et al (Kozlowski-Suzuki et al, 2009) did not find a clear relationship between GST and tolerance in copepods towards toxic phytoplankton (the dinoflagellates Alexandrium minutum, A. tamarense and Prorocentrum lima, and the haptophyte Prymnesium parvum). In their study, the phytoplankton contained nodularin, toxins causing paralytic shellfish poisoning and diarrhetic shellfish poisoning, and ichthyotoxins with haemolytic activity instead of MC.…”
mentioning
confidence: 94%
“…However, the total activity of mGST is lower than that of sGST, as is, presumably, its contribution to the detoxification. Similarly, in Daphnia carinata, decreasing GST (total) with age was associated with higher mortality and reduced tolerance towards toxic cyanobacteria (Guo and Xie, 2011).…”
mentioning
confidence: 94%
“…In contrast, Ortiz‐Rodríguez et al showed that 7‐d exposure of the parental generation to microcystins induced higher activity of GST, CAT, and malate dehydrogenase in the offspring, and that this transgenerational effect is an important mechanism in D. magna that explain the acquirement of enhanced tolerance over generations. Guo and Xie also demonstrated that GST activity depended on the age of Daphnia carinata and on the concentration of Microcystis cells in the diet (20–60% mixed with Scenedesmus ), decreasing with age and cell concentration.…”
Section: Discussionmentioning
confidence: 96%
“…GST activity has been shown to decrease with age in Daphnia carinata, which was dependent on the food availability (Guo and Xie 2011). Although there is no information regarding the mechanisms controlling GST induction in Daphnia, the limited literature available shows that GST activity induction can be observed under different chemical stress conditions.…”
Section: Discussionmentioning
confidence: 99%